The role of attitudes to, and the frequency of, domestic violence encounters in the healthcare professionals' handling of domestic violence cases - Zorjan Saša; Smrke Urška; Šprah Lilijana (Sciendo, 2017)
Domestic violence is recognized as a public health problem with a high prevalence in the general population. Healthcare professionals play an important role in the recognition and treatment of domestic violence. Hence, conducting research on factors that facilitate or inhibit appropriate actions by healthcare professionals is of the upmost importance. The objective of the study was to examine the relationship between healthcare professionals' attitudes toward the acceptability of domestic violence and their responses when dealing with victims of domestic violence.